2021
DOI: 10.1111/clr.13839
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of novel digital workflow and dynamic navigation for single‐implant immediate loading in aesthetic zone: 1‐year prospective case series

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercialLicense, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…A split‐mouth randomized clinical trial (RCT) evaluated the accuracy of dynamic navigation compared with the unassisted freehand method and concluded that utilizing a computer‐guided technique increased accuracy significantly (Aydemir & Arısan, 2020). Although few pilot studies have introduced digital flow integrating dynamic navigation for immediate implant surgery (Kuo, Lin, Hung, Chiu, & Kuo, 2022; Pozzi, Arcuri, Carosi, Nardi, & Kan, 2021), there is a paucity of adequately powered clinical trials to elucidate the efficacy of MV‐DN‐assisted immediate implant placement.…”
Section: Introductionmentioning
confidence: 99%
“…A split‐mouth randomized clinical trial (RCT) evaluated the accuracy of dynamic navigation compared with the unassisted freehand method and concluded that utilizing a computer‐guided technique increased accuracy significantly (Aydemir & Arısan, 2020). Although few pilot studies have introduced digital flow integrating dynamic navigation for immediate implant surgery (Kuo, Lin, Hung, Chiu, & Kuo, 2022; Pozzi, Arcuri, Carosi, Nardi, & Kan, 2021), there is a paucity of adequately powered clinical trials to elucidate the efficacy of MV‐DN‐assisted immediate implant placement.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous development of digital technologies led to a more comprehensive pre-surgical evaluation of the implant recipient site, avoiding bad results during follow-up period [3,4]. The introduction of the cone-beam computed tomography (CBCT) scan, the ongoing development of intraoral optical scanners (IOS) and modeling softwires allowed the clinician to digitally navigate through the three-dimensional (3D) bone and soft tissue architecture of the virtual patients into implant-planning software [5,6]. Implant positioning was more predictable and accurate since template-assisted surgery was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…36 The use of a different navigation system in socket shield technique was previously published in a clinical case report in which the author performed a 1-mm diameter osteotomy from the endodontic chamber to the root apex, reporting successful outcomes and completed the procedure free-hand. 37 In the present study, all the critical steps of the socket-shield technique were executed with navigation system dynamic guidance, and in par- decreased if the thickness of the root fragment increases. 27 Despite the root-shield thickness is still a controversial issue some authors reported that it is not advisable below 1.5 mm because it could affect the root stability.…”
Section: Resultsmentioning
confidence: 99%
“…The surgical handpiece and patient tracking arrays were calibrated before surgery . 37 The software algorithm of navigation system automatically generated a link between patient tracking array geometry and CBCT images of the fiducials to match the real and virtual patients together. Handpiece and patient tracking arrays must be detected continuously by the two overhead stereo cameras to allow a consistent triangulation between preoperative planning and tracking coordinate systems, leading to their precise position and orientation in a common coordinate path during the surgery.…”
Section: Methodsmentioning
confidence: 99%